Incidence and Risk Factors Associated with Early Pregnancy Loss in Thoroughbreds. (September 2014) - Rose, B.; Firth, M.; Morris, B.; Nicholson, C.; Verheyen, K.; Wathes, D.C.; de Mestre, A.M.
Abstract : Reasons for performing study: Early pregnancy loss (EPL) between Days 15 and 65 of pregnancy occurs in 7–10% of Thoroughbred pregnancies causing substantial financial losses. Despite this, very little is known about risk factors associated with the condition. Objectives: To determine the current incidence of EPL in Thoroughbred mares and to investigate risk factors associated with the condition. Study design: A prospective cohort study was carried out on a population of 927 Thoroughbred mares in the Newmarket area during the 2013 breeding season. Methods: Questionnaires were completed by clinicians from 2 veterinary hospitals and stud secretaries from 23 stud farms. Univariable risk factor analyses were conducted using Chi‐squared and t tests. Results: The incidence of pregnancy loss was 6.8% (95% confidence interval [CI] 5.3–8.6%) between Days 15–42 and 2% (95% CI 1.2–3.0%) between Days 43–65. Mares aged 11 years or over were 2.4 times more likely to suffer EPL than younger mares (95% CI 1.5–3.9): the risk of loss increased as mare age increased. Foaling, rested or barren mares had a 4.3 times increased risk of loss compared to maiden mares (95% CI 1.5–12.0). Mares receiving the preovulatory hormones deslorelin or hCG were shown to have a significantly reduced risk of EPL (P = 0.03) compared with mares who had not received any preovulatory treatments. Pregnancies undergoing loss had a significantly smaller vesicle size (mean 1.7 cm, s.d. 0.51) at the initial (Day 14–17) pregnancy scan compared to pregnancies which were maintained throughout the study period (mean 2.0 cm, s.d. 0.49, P = 0.01). Conclusions: The incidence of EPL in 2013 was similar to that previously reported in the Newmarket area. Further multivariable risk factor analyses and investigations to discover novel causes of EPL are required to reduce the incidence of this condition. Acknowledgements: Newmarket Equine Hospital, Rossdales Equine Practice. Ethical animal research: This study was approved by the Royal Veterinary College's Ethics and Welfare Committee.Sources of funding: Thoroughbred Breeders Association.Competing interests: None.